Using Health Belief Model Constructs to Examine Differences in Adherence to Pap Test Recommendations among Iranian Women - Karimy, Mahmood (Asian Pac J Cancer Prev, 2017)
Despite documented successful Pap tests in routine care of women, screening levels are unfortunately often lower than recommended. This study aimed to assess differences in adherence to Pap test guidelines among a sample of Iranian women using the Health Belief Model (HBM). In this descriptive and analytical study, information was collected from a total of 305 women, (age range of 15-49) from Zarandieh health centers in Iran using a random multistage sampling method. The questionnaire covered demographic characteristics; health belief model constructs were gathered by a self-report method. The results were analyzed using the independent samples t test and logistic regression in SPSS-20. A total 32% of the subjects had a history of a Pap test and the score mean of the whole constructs model (knowledge, susceptibility, severity, benefits, barriers and self-efficacy) in these individuals was higher than those without a positive history. Among the predictive variables of HBM constructs, the highest weights were observed for perceived benefits ß)=0.36), perceived susceptibility =ß) 0.35) and self-efficacy ß)=0.29). Based on our finding of positive relationships for health belief model structures with performance of a pap smear test, designing educational interventions for changing the knowledge levels and beliefs of women is recommended.